Holoprosencephaly, proboscis and anophthalmia in a foetus with matUPD14 and trisomy 13. First case to be diagnosed with hysteroscopy: A case report. Issue 3 (2019) - Iliana, Lalou; Fani, Gkrozou; Meridis, Eleftherios; Orestis, Tsonis; Minas, Paschopoulos; Marika, Syrrou
No abstract available